New semionotiform (Actinopterygii: Neopterygii) from the Late Jurassic of southern Germany - López-Arbarello, Adriana (2011)
We report on a new semionotiform taxon, Scheenstia zappi gen. et sp. nov., from Schamhaupten in the Late Jurassic limestones of the Franconian and Swabian Alb, southern Germany. Although the taxon is so far represented by a single specimen, excellent preservation allows a detailed description of its skeletal anatomy. Scheenstia zappi is distinguished by the presence of a sensory canal in the supraorbital bones and a saddle-like articular surface in the quadratojugal, both features so far unknown in other semionotiforms. The new taxon is further diagnosed by a unique combination of characters: More than three pairs of extrascapular bones; frontals less than three times longer than their maximal width; semitritorial dentition; four anterior infraorbitals; middle pit line contained in a groove in the dermopterotic and parietal; concave posterior border of the angular, robust bugle-like process of the posttemporal bone; large basal fulcra; eleven fin rays in the lower lobe of the caudal fin (below the lateral line); and a first, scale-like caudal fin ray reduced. Among semionotiforms it most closely resembles Lepidotes, in particular the large tritorial forms of the Late Jurassic and Early Cretaceous of Europe, such as L. mantelli, L. maximus and L. laevis. The peculiar shape of the quadratojugal in Scheenstia zappi resembles the condition in some basal teleosts in which a ventral articular surface of the quadrate probably served in the rotation of the lower jaw. Copyright © 2011 The Natural History Museum.